2010
DOI: 10.1007/s13213-009-0008-5
|View full text |Cite
|
Sign up to set email alerts
|

CO in methanogenesis

Abstract: Although CO is present in methanogenic environments, an understanding of CO metabolism by methanogens has lagged behind other methanogenic substrates and investigations of CO metabolism in non-methanogenic species. This review features studies on the metabolism of CO by methanogens from 1931 to the present. The pathways for CO metabolism of freshwater versus marine species are contrasted and the ecological implications discussed. The biochemistry and role of CO dehydrogenase/acetyl-CoA synthase in the pathway … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 100 publications
1
20
0
Order By: Relevance
“…F 420 regeneration during growth on carbon monoxide. Both M. acetivorans and M. barkeri grow on carbon monoxide by oxidizing it to CO 2 and subsequently reducing CO 2 to methane (21). In methanogens, the reduction of carbon dioxide to methane requires the oxidation of two equivalents of reduced coenzyme F 420 .…”
Section: Model Reconstructionmentioning
confidence: 99%
See 2 more Smart Citations
“…F 420 regeneration during growth on carbon monoxide. Both M. acetivorans and M. barkeri grow on carbon monoxide by oxidizing it to CO 2 and subsequently reducing CO 2 to methane (21). In methanogens, the reduction of carbon dioxide to methane requires the oxidation of two equivalents of reduced coenzyme F 420 .…”
Section: Model Reconstructionmentioning
confidence: 99%
“…Ech hydrogenase is not present in the M. acetivorans genome, and although an frh operon is present, it does not encode a functional enzyme (24). Thus, the mechanism for F 420 regeneration in M. acetivorans during growth on CO remains unknown (21).…”
Section: Model Reconstructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon monoxide (CO) has proven to be more inhibitory to methanogenesis than to hydrogenogenesis (i.e., H 2 -production), acetogenesis, and solventogenesis (i.e., acetate and alcohol production, respectively) at mesophilic and thermophilic temperatures (Ferry, 2010;Guiot, Cimpoia, & Carayon, 2011;Rother & Metcalf, 2004;Sipma et al, 2003). A few studies on this topic have reported enhancement of acetogenesis and inhibition of methanogenesis at CO partial pressures (P CO ) ≤ 0.3 atm (Alves et al, 2013;Guiot et al, 2011;Luo et al, 2013).…”
mentioning
confidence: 99%
“…In addition to these two well-known ways of producing methane, it can be produced similarly from substrates such as formic acid, methanol, methylamine or carbon monoxide [115][116][117][118]. It was long assumed that about 70% of total methane formed during biogas production stems from acetoclastic methanogenesis and the main prokaryotes responsible for this reaction are Methanosarcina spp.…”
Section: Microbiology and Biochemistry Of Cassava Biogas Productionmentioning
confidence: 99%